Sources of Debt Accumulation in a Small Open Economy - Senhadji, Abdelhak (IMF Working Papers; Working Paper ;, 1997)
This paper analyzes the borrowing behavior of a small open economy of a developing country that relies heavily on imports for its capital formation and faces an upward-sloping supply function of foreign loans. Decision makers face uncertainty about the longevity of external shocks. That uncertainty generates forecast errors that lead to substantial debt accumulation. It is found that the assumption of an upward-sloping supply function of foreign loans, which is a more realistic formulation for developing countries than the usual perfect elasticity, offers an alternative to the Uzawa-type utility function for analyzing asset accumulation in the small open economy framework.